ARCHIVE MANAGEMENT IN THE DIGITAL ERA: CASE STUDY OF ADMINISTRATION OF SMA NEGERI 4 SIDOARJO - Lailul Mursyidah; Ilmi Usrotin Choiriyah; Ari Nur Aliyah Rohalia (PT. Antis International Publisher, 2024)
Background: Effective records management is a critical component of administrative efficiency in educational institutions, especially in the digital era where rapid access to accurate information is essential for school operations and accountability. Specific Background: SMA Negeri 4 Sidoarjo provides a representative case for examining the current state of records management within Indonesian public high schools, particularly in the context of transitioning from manual to digital systems. Knowledge Gap: While records management has been widely discussed in the context of corporate and government institutions, limited research has been conducted on its implementation, challenges, and development strategies in the education sector, especially at the high school level. Aims: This study aims to analyze the effectiveness of records management practices in the administrative section of SMA Negeri 4 Sidoarjo, identify key challenges, and propose strategic recommendations for improvement. Results: The study reveals several ongoing challenges, including limited availability of digital records, slow retrieval processes, weak information security measures, and inadequate human resources and infrastructure. These factors collectively hinder the effectiveness of administrative recordkeeping. Novelty: This research offers one of the first in-depth qualitative evaluations of school-based records management practices in an Indonesian high school setting. It provides insights into the transitional issues faced by educational institutions in adopting digital documentation systems. Implications: The findings suggest the need for a comprehensive records digitization initiative, the development of an integrated digital records management system, upskilling of administrative personnel, and improved investment in technological infrastructure. These recommendations serve as a strategic guide for educational institutions aiming to modernize administrative practices in alignment with digital transformation goals.